THE LEGAL ASPECTS OF HIGHER EDUCATION IN THE REPUBLIC OF MACEDONIA AND THEIR IMPLICATIONS ON TEACHING AND LEARNING - Zejneli, Ismail; Shasivari, Jeton; Kareva, Veronika (European Scientific Journal, ESJ, 2013)
In this paper, the authors analyze the legal and legislative aspects of higher education in the Republic of Macedonia (RM) and their implications in the teaching and learning process. In this regard, the paper will address the issue of the legal definition of the structure and content of study programs as well as setting the legal criteria for advancement in teaching that is the minimum number of publications published in specific journals and types of magazines. These issues are analyzed in the light of university autonomy guaranteed by the Constitution of the Republic of Macedonia. Research component of the paper aims to seek adequate answer to the question of to what extent such legal provisions contribute to the learning process more efficient and teaching based on the active participation of students and the creation of possible learning outcomes that match their needs. Working on three key approaches: theory, legislation and practice this paper tries to bring concrete findings on the difficulties of implementing legal solutions by the professors in their academic settings and to provide appropriate suggestions and recommendations about some of the most rational legislation solution in this regard.